Immunophenotyping of septic shock patients with endotheliopathy: focus on monocyte subtypes and Immune regulatory molecules - Al-Haidar, Saif; Schønemann-Lund, Martin; Gybel-Brask, Mikkel; Stensballe, Jakob; Andresen, Lars; Johansson, Pär I.; Bestle, Morten H.; Skov, Søren (Frontiers in Immunology, 2025)
BackgroundSeptic shock is characterized by dysregulation of the host response to infection which results in life-threatening organ dysfunction that can be partly attributed to immune alterations and endothelial dysfunction (endotheliopathy). This lethal condition is dynamic, complex, and heterogeneous.AimThus, an exploratory broad phenotypic and functional analysis of circulating immune cells and mediators were carried out to better understand the role of the immune system in a subgroup of septic shock patients with endotheliopathy defined by increased levels of soluble thrombomodulin (sTM). In this regard, especially the immune status of monocyte subtypes (classical, intermediate, and nonclassical) was investigated for surface thrombomodulin (TM), MHC class II molecules (HLADR, -DQ, and -DP) and immunomodulatory surface receptors (TREM-1, CD137, VISTA, HVEM and BTLA).Result and conclusionOur comprehensive immunophenotypic analysis on a septic shock cohort with endotheliopathy identified distinct immune perturbation patterns that potentially can lead to novel treatment avenues in the management of this life-threatening condition.